Peran Sanggar Tari Zundarima Dalam Mengembangkan Tari Tradisional di Kabupaten Tangerang - Widyastuti, Sephia Dwi; Purwinarti, Wiwin; Tiyas, Wahyuning (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2025)
Sanggar Tari Zundarima is developing traditional dance in Tangerang Regency and this research’s objective is to dig into the role of Sanggar Tari Zundarima in developing the traditional dance. This research is conducted using the qualitative method which uses descriptive approach and data collection method through obsercation, interviews, and documentation including analysis conducted by data reduction, data presentation and data verification. Based on the research, the role of the Sanggar Tari Zundarima to develop traditional dance involves dancer and the Tangerang Regency Department of Culture. Some of the traditional dance developed for the Tangerang Regency which is acknowledged by the DISPORABUDPAR is the Bentang Gemilang dance and the Babad Tangerang dance. Other dances such as the Kinking Banten dance, Hayam Wareng dance and others are still ongoing registration process. The strategy used involves economic strategy which consists of management strategy, investment and business which is using proximity approach and promotion while also using training strategy and development strategy.